Harmonizing Legal Frameworks: A Comparative Legal Overview of Employee Transfers in Albania and Selected EU Countries - Kau, Renata; Gjika, Jonida (European Scientific Journal, ESJ, 2024)
Employee transfer is an important phenomenon that impacts both the public and private sectors worldwide. It is one of the most important managerial and productive instruments that a company can use. Although it is commonly practiced, the institution of internal employee transfers is not regulated in the Labor Code of Albania. Albanian legislation only recognizes the internal transfer of one category of employees, the civil servants. In this regard, there arises an urgent need for the immediate regulation of this institution for the other categories of employees as well. In the context of Albania’s accession to the European Union, implementing such regulations would ensure effective protection for employees in accordance with European legislation. Without such regulation, transfers could become a mechanism that employers might misuse. This research paper employs various scientific methods, including historical, analytical, and comparative methods. Following a historical analysis of Albanian legislation, the paper examines employee transfers under current Albanian laws and those of selected EU countries. In conclusion, it is essential for the Albanian Labor Code to establish regulations for internal employee transfers that align with leading European legislations, which have often served as models for shaping Albanian law.